Motivation of School Administrators and Teacher Performance in Insular Areas of Sulu Province - Ijing-Jalaidi, Nagra K. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research is an examination of the relationship between school administrator job motivation and teacher performance in the outlying areas in the Sulu Province particulazrly Jolo district. Schools in remote locations may experience constraints such as resource limitations, social-politcal unrest, and logistic obstacles. In this context, the study examines whether APT motivation of Administrators impacts teacher effectiveness and school climate. The study used a descriptive-correlational survey design with 90 teachers and 10 administrators being utilized as data respondents through structured interviews. In the survey, agreement is achieved by the teachers with all interpretations of motivated administrators, although performance appears generally to be limited to motivation. Salient motivational practices were professional rewards, organizational support, and self-development experiences. In addition, collaborative, transformational influential leadership styles with open communication were found to be enhancing teacher engagement and improving instructional performance. Despite geographical and resource constraints, the motivation of administrators was high and it reflected increased teacher effectiveness. In order to address these issues further, it was suggested that different strategies, e.g., enhanced training programs, inter-school cooperation, and equitable resource allocation be implemented. The results emphasize the importance of motivated managers in maintaining teacher productivity and teaching quality in disadvantaged and hard-to-reach areas. The author indicates that to improve teacher dedication and student learning effects, the enhancement of leadership motivation is required. Recommendations are for policy reforms, enhanced communication and community involvement strategies to give support for school leadership in insular provinces such as Sulu.